2007
DOI: 10.1016/j.bbmt.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Survival Outcome after Hematopoietic Stem Cell Transplantation for Hematologic Malignancies According to Area of Primary Residence

Abstract: We evaluated whether or not a patient's area of primary residence is an independent risk factor for overall survival (OS) after HLA-identical sibling or autologous hematopoietic stem cell transplantation (HSCT). This retrospective cohort study included patients who underwent autologous (n = 1739) or HLA-identical sibling (n = 267) HSCT to treat a hematologic malignancy between 1983 and 2004 at the University of Nebraska Medical Center. Primary area of residence, using the patient's zip code, was categorized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…Our results partially confirm those of a previous study by Rao et al 3 Their study showed a significant increase in mortality in rural patients undergoing autologous transplantation, but not in patients undergoing allogeneic transplantation. They postulated that this might be due Urban vs rural outcomes in BMT K Paulson et al to different follow-up patterns of patients undergoing autologous and allogeneic transplantation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results partially confirm those of a previous study by Rao et al 3 Their study showed a significant increase in mortality in rural patients undergoing autologous transplantation, but not in patients undergoing allogeneic transplantation. They postulated that this might be due Urban vs rural outcomes in BMT K Paulson et al to different follow-up patterns of patients undergoing autologous and allogeneic transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…An American study 3 has shown that living in rural areas is associated with increased mortality in patients receiving autologous BMT, but not allogeneic BMT. The authors postulated that the absence of a relationship among allogeneic BMT patients may be because of a small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients have shown increased unwillingness to travel long distances for post-transplant care, resulting in care being avoided or shifted to primary care physicians or oncologists located nearer to the patient, but having limited experience with transplant care. 7 For HCT, both the geographic and non-geographic components of access, as well as population and system-level factors, appear to have significant roles in both utilization and outcomes. Disparities in access to HCT services have been reported for minority and/or socially disadvantaged populations, 12,13 as well as difficulties in securing a suitable donor 14 and limited evidence of worse overall outcomes after HCT.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other research suggests a greater posttransplant mortality risk for autologous transplant patients residing in rural regions (longer travel time to HCT service location) when compared with those from urban regions. 7,8 The relatively small number of HCT facilities in the United States, in conjunction with the potential effects of geographic access on HCT utilization and outcomes, highlight the importance of understanding the current state of geographic access to HCT services. This research evaluates the status of potential geographic access to HCT facilities using national-level roads and population databases within a Geographic Information System.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that are perceived to be less important within the Canadian context may be in contrast with the factors recently described in the literature. In particular, distance from the transplant center has been reported to negatively influence transplant outcomes in several studies, 6,7 including a study performed in Canada, 8 but was deemed less important than other factors in our survey. It is likely that greater importance of resource utilization, including the cost associated with cord blood unit acquisition, would be rated more highly by transplant program directors or administrators who oversee transplant program expenditures and this population was not specifically targeted in our survey.…”
mentioning
confidence: 86%